Orbital Tumors - Retrospective Study of 24 Years - Muhammad Shaikh, Abdul Rehman Siyal, Faiz M. Halepota, Khalid Iqbal Talpur, Mahesh Kumar Luhano Late Sher (Pakistan Journal of Ophthalmology, 2018)
Purpose: To evaluate incidence of uncommon tumors with unique clinical presentation and rising incidence of Lymphomas. Material and Methods: This study was conducted at Chandka Medical College Larkana, Peopled Medical College, Nawabshah; Liaquat University of Medical and Health Sciences, Eye Hospital, Hyderabad; and two private hospitals of Sindh province namely Hajiani Hospital, Pathan Colony Hyderabad; and, Hayat Medical Center, Satellite Town Mirpurkhas. A total of 42 cases and conditions simulating tumors were identified and in all cases diagnosis was confirmed by histology. Results: A rising incidence of Lymphoma, 06 cases (2.52%), followed by tumors of eyeball and lids (squamous cell CA, Retinoblastoma) 06 cases each (2.52%) were noted. Fibroangio sarcoma 03 (1.26%) lacrimal gland tumor 03 (1.26%), socket tumors 03 (1.26%) Nerve sheath tumor 03 (1.26%) (schwannoma and Neurofibroma) porocarcinoma and metastatic tumor one case each were identified (0.42%). Miscellaneous non malignant lesions were 08 (3.36%) Lymphoid Hyperplasia of lacrimal gland 02 case (0.84%). Conclusion: Our study shows variety of tumors, few uncommon which affect orbit, with lately rising incidence of Lymphomas, revealed by employing modern investigation techniques. Ever increasing incidence of orbital lymphoma need to be confirmed by further studies in future.